2017
DOI: 10.2147/ijn.s122842
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of green-synthesized silver nanoparticles depends on the applied natural extracts: a comprehensive study

Abstract: Due to obvious disadvantages of the classical chemical methods, green synthesis of metallic nanoparticles has attracted tremendous attention in recent years. Numerous environmentally benign synthesis methods have been developed yielding nanoparticles via low-cost, eco-friendly, and simple approaches. In this study, our aim was to determine the suitability of coffee and green tea extracts in green synthesis of silver nanoparticles as well as to compare the performance of the obtained materials in different biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 38 publications
(41 reference statements)
6
99
0
1
Order By: Relevance
“…8,12 Green alternatives to harsh reducing chemicals and environmentally benign capping agents have also been developed to reduce the costs of nanoparticle production and to minimize the generation of hazardous wastes upon the synthetic procedures. 13 In a comprehensive study on AgNPs obtained by chemical reduction using coffee and green tea extracts, we proved the remarkable antimicrobial efficiency of such particles, 14 and we showed evidence that the green material used for AgNP synthesis can largely define the physical, chemical and biological characteristics of the produced nanomaterial. 14 Owing to widespread applications, there is an ever-growing demand for AgNPs and AuNPs, while the challenges of their economical, environmentally safe and sustainable production should also be addressed.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…8,12 Green alternatives to harsh reducing chemicals and environmentally benign capping agents have also been developed to reduce the costs of nanoparticle production and to minimize the generation of hazardous wastes upon the synthetic procedures. 13 In a comprehensive study on AgNPs obtained by chemical reduction using coffee and green tea extracts, we proved the remarkable antimicrobial efficiency of such particles, 14 and we showed evidence that the green material used for AgNP synthesis can largely define the physical, chemical and biological characteristics of the produced nanomaterial. 14 Owing to widespread applications, there is an ever-growing demand for AgNPs and AuNPs, while the challenges of their economical, environmentally safe and sustainable production should also be addressed.…”
Section: Introductionmentioning
confidence: 81%
“…13 In a comprehensive study on AgNPs obtained by chemical reduction using coffee and green tea extracts, we proved the remarkable antimicrobial efficiency of such particles, 14 and we showed evidence that the green material used for AgNP synthesis can largely define the physical, chemical and biological characteristics of the produced nanomaterial. 14 Owing to widespread applications, there is an ever-growing demand for AgNPs and AuNPs, while the challenges of their economical, environmentally safe and sustainable production should also be addressed. A rapidly progressing area of nanobiotechnology is the microbe-assisted nanoparticle synthesis, 15 where bacterial strains, yeast-and alga-mediated reactions are exploited for nanoparticle generation.…”
Section: Introductionmentioning
confidence: 81%
“…26,27 This corona serves as a kind of biological identity of the nanoparticle; moreover, it contributes to colloidal stability as the protein-rich corona can counteract the abovementioned disruptive environmental conditions, also demonstrated by Tai et al and Alarcon et al 28,29 In our recently published papers, we described environmentally benign synthesis approaches for green nanomaterial formation, and we also showed that the various green materials used for stabilization and for reduction of metal ions have a defining role in determining and fine-tuning the biological activity of the obtained green nanoparticles. 15,30,31 The scientific literature is lacking in data on the aggregation behavior, and especially its relation to the biological properties of AgNPs, as a systematic examination involving a wide variety of parameters has never been performed. Therefore, in this paper we executed a thorough analysis of this issue.…”
Section: Introductionmentioning
confidence: 99%
“…59,60 Likewise in dsRNA viruses the AgNPs after interaction with viral genome, the NPs were found to inhibit viral replication. 61 The antiviral efficacies of AgNPs by these modes of viral entry or attachment inhibition or viral replication inhibition have also been evaluated in other viruses shown in Table 1.…”
Section: Silver Nanoparticles (Agnps)mentioning
confidence: 99%